Mercury speciation by CE: a review - Kubáň, Petr; Houserová, Pavlína; Kubáň, Pavel; Hauser, Peter C; Kubáň, Vlastimil (Electrophoresis, 2007)
CE methods for the speciation of inorganic and organomercury compounds are reviewed. Sample preparation, separation conditions and detection modes are discussed. Efficient separation and sensitive determination of mercury species by CE typically involves complexation with various thiols, chromogenic and other chelating agents; however, some methods do not require complexation. Spectrophotometric detection based on UV-visible absorption is by far the most commonly used. Hyphenated techniques, such as CE/inductively coupled plasma (ICP)-MS, hydride generation coupled to ICP-MS or atomic fluorescence spectrometry and CE/atomic absorption spectrometry are gaining popularity due to their high sensitivity and selectivity. Last, but not least, the potential and applications of electrochemical methods for detection of separated mercury species are outlined.
Keywords: Environmental Pollutants; Electrochemistry; elektroforéza kapilární; spektrofotometrie atomová; sloučeniny rtuti; elektrochemie; Electrophoresis, Capillary; látky znečišťující životní prostředí; Mass Spectrometry; Mercury Compounds; Financing, Organized; financování organizované; Organomercury Compounds; hmotnostní spektrometrie; organortuťnaté sloučeniny; Spectrophotometry, Atomic